Heterotopic ossification related to the use of recombinant human BMP-2 in osteonecrosis of femoral head. Issue 27 (July 2017) - Shi, Lijun; Sun, Wei; Gao, Fuqiang; Cheng, Liming; Li, Zirong
Abstract : Abstract: Despite the wide use of recombinant human bone morphogenetic protein-2 (rhBMP-2) in bone defect, its application in treating osteonecrosis of femoral head (ONFH) is yet to be elucidated. The heterotopic ossification (HO) after rhBMP-2 usage in some orthopedic surgeries has been reported previously; however, only a few studies describe this complication in the treatment of ONFH. The present study investigated whether the rhBMP-2 application would increase the risk of HO formation in selected ONFH patients with nonvascularized bone grafting surgery and enhance the surgical results of nonvascularized bone grafting as compared to patients who did not receive intraoperative rhBMP-2. A retrospective analysis was performed on 94 patients (141 hips) who, with Association Research Circulation Osseous (ARCO) stages IIb, IIc, and IIIa ONFH, underwent nonvascularized bone grafting surgery. The first 46 patients (66 hips) received intraoperative rhBMP-2. The postoperative radiographic results (X-ray and CT scan) and Harris hip score (HHS) were reviewed in each patient to record the incidence of HO formation and evaluate the clinical efficacy of rhBMP-2, respectively. HO formation frequently occurred in patients receiving intraoperative rhBMP-2 (8/66 hips) than those not receiving the protein (1/75 hips) ( P  = .02). HHS improved from preoperatively at the final follow-up ( P  < .01) in the BMP-positive group, with a survival rate of 83.3%. In the BMP-negative group, the HHS improved from preoperatively at the end of the follow-up ( P  < .01), and the survival rate was 72.0%. rhBMP-2 has osteoinductive property and might serve as an adjuvant therapy in the surgical treatment of ONFH. However, the incidence of HO formation might increase when used in high doses.